Birth weight, Apgar scores and gentamicin were associated with acute kidney injuries in VLBW neonates requiring treatment for patent ductus arteriosus. (1st October 2018) - Aygün, Aylin; Poryo, Martin; Wagenpfeil, Gudrun; Wissing, Antonia; Ebrahimi‐Fakhari, Daniel; Zemlin, Michael; Gortner, Ludwig; Meyer, Sascha
Abstract: Aim: We assessed the risk factors for transient acute kidney injury in very low birth weight (VLBW) infants treated for patent ductus arteriosus (PDA) using the serum creatinine‐based criteria in Kidney Disease: Improving Global Outcomes. Method: This retrospective study of infants requiring ibuprofen and, or, surgery for haemodynamic relevant PDAs was performed at the University Children's Hospital of Saarland, Homburg, Germany, from January 2009 to December 2015. Results: We studied 422 infants with a mean birth weight of 1059 ± 308.2 g. Acute kidney injuries developed in 150/295 infants (50.9%) with spontaneous PDA closure, in 46/82 (56.1%) who received intravenous ibuprofen treatment, in 18/24 (75.0%) who had surgery and in 15/21 infants (71.4%) who received both medical and surgical treatment. Acute kidney injuries were associated with birth weight and gestational age, Apgar scores at 10 minutes, the PDA size corrected for birth weight, a PDA with three affected circulatory territories, PDA surgery and gentamicin. Multiple logistic regression analysis showed particular associations between acute kidney injury and birth weight (p = 0.001), the 10‐minute Apgar score (p = 0.02) and gentamicin (p = 0.043). Conclusion: Birth weight, the 10‐minute Apgar score and gentamicin were particularly associated with acute kidney injuries in our cohort.